Transformasi Budaya terhadap Perubahan Sosial Di Era Globalisasi - Guntoro (Prodi Sosiologi Agama, 2020)
This paper aims to provide an overview related to cultural transformation and social change. Socio-cultural changes in a society are a necessity and can not be avoided due to changes in society in accordance with the times. This change can be said as an effort to survive (survive) or defend themselves. In a broad sense, social movements can be interpreted as a central part of modernity. Social movements determine the characteristics of modern politics and modern society. This social movement is closely related to the fundamental structural changes that have been known as modernization that is spreading to the world system and life systems. Behind social movements in social change, there are conditions that can determine whether the social movements will succeed in making a broad impact and provide changes in the level of life as expected or not. In this condition, it will foster various other social movements.